FAKTOR PENGHAMBAT PERKEMBANGAN TARI ZAPIN MELAYU DI KOTA BATAM - Ajrina Rosada Harma; Desfiarni Desfiarni; Susmiarti Susmiarti (SENDRATASIK UNP, 2017)
AbstractThis research is classified into qualitative study which was conducted by using descriptive method. The primary has been gotten from the sources by observasing and interviewing them. The secondary data has been gotten from the documented data, documents and books, which are relevant with the research. After the data was collected, the researcher analysed the data by using data reduction, the presentation of data, and verification and conclusion. Based on the research findings, it was found that the factors impeding the development of “Zapin Melayu” Dance were derived from both the internal and external factors. The internal factor is closely related to the community in which the dance is developed. The rapid change of information nowadays has brought people to a new culture. Thus, the gradually  leave behind what they used to value as “tradition” and embrace modernity. People are not so much into learning the traditional dances anymore such as the Melayu Zapin dane. The external factors are related to the infiltration of the foreign cultures that increasingly push aside the local ones.Keywords: Obstacle Factor, Development, Dance Zapin Melayu